Prevalence and associated factors of internet addiction among Chinese adolescents: association with childhood trauma - Fan, Tianqing; Twayigira, Mireille; Song, Lintong; Luo, Xuerong; Huang, Chunxiang; Gao, Xueping; Shen, Yanmei (Frontiers in Public Health, 2023)
Introduction: Internet Addiction (IA) is common among adolescents and may have severe consequences.This study aimed to investigate the prevalence and factors associated with IA among middle school students of Hunan Province, China. Relevance between IA and childhood trauma was also explored.Methods: 1610 students were enrolled in this cross-sectional study. Data collected included demographics; internet addiction (Revised-Chen Internet addiction scale); childhood trauma (CTQ-SF); depression, anxiety, and stress symptoms (DASS-21); suicidal behaviors, as well as non-suicidal self-injury (NSSI). Cramer's V analysis, univariable logistic regression and multivariable logistic regression were used for associations and identifying independent relevance of IA respectively.The prevalence of IA was 12.8 %. Cramer's V analysis showed that IA was associated with emotional abuse, emotional and physical neglect, NSSI, suicidal behaviors, stress, anxiety and depressive symptoms, physical disorder history. Regression analysis showed that IA was independently associated with